STIMA DEI PARAMETRI DI UNA TRASFORMAZIONE CONFORME 3D (GEOmedia, 2013)
The aim of this monograph is to explain a practical method to find the seven parameters of a conformal three-dimensional (3D) transformation, commonly used for coordinate conversion between different Datums, given the coordinates of a set of points expressed in both reference systems. This issue, in particular, deals with the Bursa-Wolf transformation's parameters, also used in the operation methods supported by EPSG to perform datum transformation to WGS 84, by means of "towgs84” values. The topic is illustrated through a practical example, having as subject the transformation used to convert coordinates related to a local cadastral reference system to the global datum WGS 84. Open Source software ILWIS (Integrated Land and Water Information System) is used to perform the crucial phase relevant to estimate the Bursa-Wolf parameters.